PERLINDUNGAN TENAGA KERJA DENGAN STATUS PERJANJIAN KERJA WAKTU TERTENTU (PKWT) DALAM PERSPEKTIF UNDANG-UNDANG KETENAGAKERJAAN DI PT. SII CIKARANG - Nurhayani, Nurhayani; Azis, Rizka Amelia; Hikmawati, Elok (Lex Jurnalica, 2024)
AbstractThe increase in the use of PKWT workers is driven by the weak position of workers and high unemployment rates. Workers have no other choice but to work with PKWT status even though the work agreed upon is actually permanent. Meanwhile, from the company side, the use of PKWT workers is considered more profitable because there are not so many rights that must be fulfilled for workers with PKWT status. In practice, PKWT workers are usually given lower wages and facilities compared to workers with PKWTT status. PT. SII, as a company engaged in the development and manufacture of electronic goods, also employs PKWT workers based on fulfilling certain order targets. Protection of the welfare of PKWT workers at PT. SII Cikarang is in accordance with the Employment Law as regulated in the PKB. Dispute resolution also prioritizes consensus deliberation through bipartite institutions. Keywords: Protection, PKWT Workers AbstrakPeningkatan penggunaan pekerja PKWT seringkali didorong adanya posisi pekerja yang lemah dan tingkat pengangguran yang tinggi. Pekerja tidak mempunyai pilihan lain selain bekerja dengan status PKWT meskipun pekerjaan yang diperjanjikan tersebut sebenarnya adalah bersifat tetap. Sementara dari sisi perusahaan, penggunaan pekerja PKWT dianggap lebih menguntungkan karena hak-hak yang harus dipenuhi bagi pekerja dengan status PKWT tidak begitu banyak. Pada prakteknya pekerja PKWT biasanya diberikan upah dan fasilitas yang lebih rendah dibandingkan dengan pekerja dengan status PKWTT. PT. SII sebagai perusahaan yang bergerak dalam bidang pengembangan dan pembuatan barang elektronik juga mempekerjakan pekerja PKWT yang didasarkan pada pemenuhan target pesanan tertentu. Perlindungan terhadap kesejahteraan pekerja PKWT di PT. SII Cikarang telah sesuai dengan Undang-Undang Ketenagakerjaan sebagaimana diatur dalam PKB. Penyelesaian sengketa juga lebih mengutamakan musyawarah mufakat melalui lembagai bipartit. Kata Kunci: Surat Pernyataan Tanggung Jawab Mutlak (SPTJM), Akta Kelahiran